O processo de aquisição da linguagem escrita na educação infantil - Marinho, Ascenilma Alencar Cardoso (2014)
This research work aims to investigate in detail, the real causes that comes interfering with the acquisition of written language acquisition of children enrolled in Early Childhood Education from a school of municipal school located in the city of João Pessoa in State of Paraiba. The strategy used for data collection was the bibliographic and documentary research, besides the application of surveys, which sought to identify the initial level of students' writing. As well as evaluate whether events read and spontaneous writing occurs, but also check whether the development activities as a prerequisite uses the students' prior knowledge. For both the technical procedure guiding the qualitative survey of comparative descriptive nature and our theoretical support had the references and Ferreiro e Teberosky (1999), Soares (2013), Vygotsky (1989), as well as official documents that support early childhood education , among them: the Law of Directives and Bases of National Education - LDBN, the National Curriculum Standards Early Childhood Education (3 vol.), the Early Childhood Education Curriculum Reference - RCNEI and the National Plan for Early Childhood Education - PNEI. Given the observed results, we use intervention as an instructional sequence that included the fable genre and related aspects: to identify the letters of the alphabet; the proper use of the page; the initial process of phonological awareness and characteristics of the fable genre. We note that the use of didactic sequences in kindergarten is a feature that enables the work of acquisition of written language, enabling a greater familiarity with the literate world, a factor that will contribute to the construction of hypotheses writing, given, enabling students greater understanding of the social function of written language.